Faktor Yang Mempengaruhi Kepatuhan Minum Obat Anti Hipertensi Pada Pasien Hipertensi di Puskesmas Pekkae - Awaliah Rahmat (Vitamin : Jurnal ilmu Kesehatan Umum, 2023)
Abstract.Hypertension is one of the main risk factors for heart problems. Apart from causing heart failure, hypertension can also result in kidney failure and cerebrovascular disease. This disease is often called the silent killer because there are no symptoms and without realizing it, sufferers experience complications in vital organs. This study aims to assess factors influencing adherence to taking anti-hypertensive medication in hypertensive patients at the Pekkae Community Health Center. This research presents the characteristics of respondents, Univariate data analysis of each variable to see the relationship between the Independent Variable and the Dependent Variable using the Chi-Square test. Based on the results of research conducted in the Pekkae Community Health Center working area, it was found that there was a relationship between predisposing factors including knowledge, beliefs, values ​​and attitudes towards compliance with taking antihypertensive medication for hypertension sufferers at the Pekkae Public Health Center, Barru Regency.